Oxidative Distress in Pathogenesis of Alcoholic Liver and Its Correction - S. P. Smolina; M. M. Petrova; V. I. Sharobaro; S. V. Nikolaev; I. G. Bobrinskaya (Общая реаниматология, 2016)
The aim of the study was to evaluate the effect of the succinatecontaining antioxidants Reamberin and Cytoflavin on (1) free radical oxidation of lipids and functioning of the antioxidant system in patient with alcoholic liver disease and hepatic encephalopathy and (2) severity of hepatocellular dysfunction.Material and methods. Prospective study involved 150 patients with alcoholic liver disease divided into three groups: Group 1 (n=50), Group 2 (n=50) and the control group (n=50). Patients of two main experimental groups (Group 1 and Group 2) received antioxidants in addition to conventional basic therapy: patients of Group 1 were administered with Reamberin, whereas in Group 2 Cytoflavin was administered. Intensive care for the patients of the control group did not include any antioxidants. The study involved assessment of the clinical course of hepat ic encephalopathy, biochemical markers of hepatic cell dysfunction, and indicators of lipid oxidation and antioxi dant defense system of the body. Nonparametric statistic methods were used for evaluation of the results.Results. All examined patients had an increased intensity of free radical oxidation of lipids and low general antioxidant activity demonstrating oxidative distress. Patients from groups 1and 2 exhibited significant improve ment in cognitive and motor functions, positive dynamics of the clinical course of the disease and hepatocellular dysfunction. There was also a trend towards normalization of free radical oxidation of lipids antioxidant para metrs of blood.Conclusion. Administration of succinatecontaining drugs in alcoholic liver disease resulted in reduction of the period of patients' stay at the Intensive Care Unit and improved longterm effects manifested as prolonged periods of clinical remission of hepatic encephalopathy.